2019
DOI: 10.3390/medicina55090560
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and the Occurrence of Postnatal Depression—A Systematic Review

Abstract: Background and Objectives: During pregnancy and the postnatal period many changes occur in a woman’s body, both in mental and physical spheres. The birth of a child and a new role—of a mother—can sometimes be associated with numerous negative emotions, uncertainty, fear, anxiety, disgust, depression, or sadness. In the puerperium period, the development of baby blues or postpartum depression may occur. Postpartum depression develops within one month of childbirth and may last up to one year. Depressive disorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 71 publications
(120 reference statements)
0
46
0
4
Order By: Relevance
“…For the most highly ranked systematic reviews, the most common interventions studied evaluated involved traditional interventions such as aromatherapy, acupuncture, and rituals [ 27 , 85 , 88 , 89 ], as well as more conventional therapies such as CBT [ 30 , 39 , 95 ], physical activity [ 34 , 65 , 81 ], and pharmacological treatments [ 29 , 42 , 44 , 55 , 57 , 79 ]. Positive benefits of aromatherapy on PPD were reported in two [ 85 , 89 ] systematic reviews, but meta-analysis was not possible due to the heterogeneity of study designs therein.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the most highly ranked systematic reviews, the most common interventions studied evaluated involved traditional interventions such as aromatherapy, acupuncture, and rituals [ 27 , 85 , 88 , 89 ], as well as more conventional therapies such as CBT [ 30 , 39 , 95 ], physical activity [ 34 , 65 , 81 ], and pharmacological treatments [ 29 , 42 , 44 , 55 , 57 , 79 ]. Positive benefits of aromatherapy on PPD were reported in two [ 85 , 89 ] systematic reviews, but meta-analysis was not possible due to the heterogeneity of study designs therein.…”
Section: Resultsmentioning
confidence: 99%
“…3e). For the most highly ranked systematic reviews, the most common interventions studied evaluated involved traditional interventions such as aromatherapy, acupuncture, and rituals [27,85,88,89], as well as more conventional therapies such as CBT [30,39,95], physical activity [34,65,81], and pharmacological treatments [29,42,44, Fig. 2 The Characteristics of the AMSTAR Assessment of Included Studies.…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…Penelitian lain juga mengemukakan hal serupa bahwa ada hubungan antara aktifitas sedang sampai berat dengan depresi postpartum [8]. Aktifitas fisik dapat menjadi faktor penting dalam pencegahan gangguan depresi postpartum [9]. Sehingga tujuan penelitian ini adalah mengetahui pengaruh karakteristik responden dan aktifitas fisik terhadap risiko depresi postpartum.…”
Section: Pendahuluanunclassified
“…Other studies showed that initiation of aerobic exercise during the postpartum period reduced the symptoms of mild depression [ 31 , 32 ]. However, some studies reported contradictory findings regarding the effect of antenatal exercise on PPD [ 30 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. These contradictory results could be explained by the type, intensity, frequency, and duration of the physical activity.…”
Section: Introductionmentioning
confidence: 99%